Is WhatsApp a 'new age advertising tool'?. (15th February 2022) - Srivastava, Mallika; Fernandes, Semila
With the emergence of social media, many organisations have started using social media platforms such as WhatsApp, Facebook, and Twitter for their marketing communication campaigns (Merlio, 2017). Given that today's consumers are considered digital natives and comprise the Generation C segment (born from 1982 to late '90s/early '00s termed as the psychographic group) (Forbes, 2018), one might suspect this group to be active in creating and disseminating product knowledge within social groups. This paper is an attempt, at studying the Generation C of urban consumers towards acceptance of WhatsApp as a tool for publicising product information, and the impact of viewer's reaction on watching the advertisements on WhatsApp towards their viral intention. The analysis of the dimension of the viewer response profile (VRP) scale posited that consumers weighed the dimension of 'confusion' the highest, and 'brand reinforcement' as the weakest predictor of VRP. Additionally, 'time spent on WhatsApp' had significant impact on 'viral intention'. 'Gender' and 'time spent on WhatsApp' partially moderated the relationship between 'viewers' affective reaction' and 'viral intention'.